Agricultural Pesticide Spraying Robot - Prathmesh Sonawane; Prathmesh Nagawade; Ajit Pharate; Prof. Omase Baburao; Dr. Sudhir Divekar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper presents the design and development of a smart agricultural pesticide spraying robot based on the ESP32 microcontroller platform. The system integrates an L298N motor driver for mobility, a DHT11 temperature and humidity sensor for environmental monitoring, and a DC water pump motor for pesticide spraying. The proposed system automates pesticide spraying to minimize human exposure to harmful chemicals and improve resource efficiency. The robot operates semi-autonomously, monitoring environmental conditions in real time and activating the spray system as needed. The solution aims to support precision agriculture through conditional pesticide application and remote operability.